Impact of Parasitic Components on EMI Generated by SMPS - Milind Madhava Jha; Kunj Behari Naik; Shyama Pad Das (International Journal of Power Electronics and Drive Systems (IJPEDS), 2012)
The ideal switching converter whether hard switching or soft switching, produces negligible EMI. Basically, the parasitic components are responsible for the generation and propagation of EMIs. This fact cannot be verified by noise measurement of a SMPS prototype because parasitic components are an inseparable part of it. This paper describes the results of EMI noise measurement of ideal simulated converters. The parasitic components are then introduced one by one. Noise measurements are done after every addition and compared with the initial result.DOI: http://dx.doi.org/10.11591/ijpeds.v2i3.789